PHYTOCHEMICAL CONSTITUENTS AND INVITRO ANTIBACTERIAL ACTIVITY OF VARIOUS EXTRACT OF AZARDIRACHTA INDICA (NEEM) - Gnanakalai, Kannusamy; Gopal, Rengaswamy (International Journal of Current Pharmaceutical Research, 2016)
Objective: To perform GC-MS analysis and to evaluate the antibacterial activity of Azadirachta indica bark. Methods: The dried powdered bark of Azadirachta indica (5g) were extracted exhaustively by crude and then fractionated into water, acetone, chloroform and ethanol. The bark ethanol extract was analyzed by GC-MS to identify and characterize the chemical compounds present in the crude extracts. Results: Ethanol extract was found to contain the highest zone of inhibition against E. coli. In vitro antibacterial activities of ethanol extract were significant and comparable with the other extracts. Hence, the ethanol extract was selected for GC-MS and to identify the presence of 5 compounds in ethanol extracts. Conclusion: Findings from this study state that the plant Azadirachta indica can be a potent source for treating diverse medicinal properties especially infectious diseases.